Diversity of Root Nodule-Associated Bacteria of Diverse Legumes Along an Elevation Gradient in the Kunlun Mountains, China - Pang, Jinfeng; Palmer, Marike; Sun, Henry J.; Seymour, Cale O.; Zhang, Ling; Hedlund, Brian P.; Zeng, Fanjiang (Frontiers in Microbiology, 2021)
Bacteria in root nodules of legumes play important roles in promoting plant growth. In this study, we investigated root nodule-associated bacteria isolated from leguminous plants along an elevation gradient on the northern slope of the Kunlun Mountains, China, using a cultivation approach. In total, 300 isolates were obtained from seven legume species within six ecological zones. Isolates were identified based on 16S rRNA gene phylogenetic analysis and potential rhizobia were further identified using a recA gene phylogeny. Among the isolates, Bacillales (particularly Bacillus) were the dominant isolates from all host legumes and all elevations (63.5%), followed by Rhizobiales (13%) and Pseudomonadales (11.7%). Less than 3% of the isolates belonged to Burkholderiales, Paenibacillales, Enterobacteriales, Actinomycetales, Sphingomonadales, Xanthomonadales, Chitinophagales, Brevibacillales, Staphylococcales, or Mycobacteriales. A few elevation-specific patterns emerged within the Bacillales and Pseudomonadales. For example, isolates related to the psychrotroph Bacillus psychrosaccharolyticus were only isolated from the highest elevation sites (>3,500 m) whereas those related to the mesophile Bacillus endophyticus were only isolated from lowest elevation sites (1,350 m), suggestive of a role of soil temperature in their distribution. Similarly, isolates related to Pseudomonas brassicacearum were the dominant Pseudomonadales isolates, but they were only isolated from middle and low elevations (<3,200 m). A total of 39 isolates belonged to the Rhizobiales, 36 of which were confirmed to the genus level using the recA gene. In all, Rhizobiales isolates were obtained from five different host legumes spanning the entire elevation gradient. Those from the low-elevation Qira Desert-Oasis Transition Zone (1,350-1,960 m) suggested some patterns of host preference. For example, most isolates from Albizia julibrissin formed a monophyletic group related to Rhizobium lemnae and most from Alhagi sparsifolia were closely related to Ensifer kummerowiae. In general, this study shows that most bacteria associated with root nodules of legumes are widely distributed in distinct ecological zones within a single geographic region but suggests that both climate and host interactions may influence their distributions.